INTERVENSI RUSIA TERLIBAT DALAM PROSES RE-UNIFIKASI MOLDOVA DAN RUMANIA - Nasution, Enda Gustrin P; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is a study of diplomacy which discussing about Russia's intervention process Reunification of the territory Moldova and Romania. The collapse of the Soviet Union in late 1980s surfaced a variety of movement due to the policy of political nationalism